PROGRAM PENYULUHAN TERPADU DALAM PENINGKATAN DERAJAT KESEHATAN SANTRIWATI TERHADAP PERMASALAHAN KESEHATAN SANRIWATI DIPONDOK PUTRI BINBAZ PIYUNGAN BANTUL - Maulida Rahmawati Emha; Farida Afifah Ibnatun ZM (ABDIMAS Madani, 2019)
Binbaz female Islamic boarding school is classified into one particular group in community nursing, because it has homogeneous population characteristics and the same age limit in a particular area. The purpose of implementing this integrated counseling program is to: improve students' knowledge about health related to clean and healthy lifestyles, improve the health status of the students with the hope to prevent diseases and not to recur with better lifestyle and behavioral changes. Method of implementing activities by conducting: (1) assessing health problems faced by the students, (2) Planning community service activities and (3) giving extension education activities for health education in stages and continuously for 1 semester. This activity is expected to improve the health status of Binbaz female islamic boarding school students